Persepsi Risiko Kontaminasi Merkuri pada Pekerja Penambangan Emas Skala Kecil (PESK) di Kecamatan Limun - Agustin, Rista; Muhammad, Damris; Kalsum, Ummi (Universitas Batanghari Jambi, 2024)
Small-scale Gold Mining (ASGM) in Limun Sub-district has caused a decline in the quality of Batang Limun River in the form of increasing mercury levels from 0.18 ppb to 0.30 ppb in 2015, which can have an impact on public health in the mining area. A risk perception assessment needs to be conducted to formulate effective risk communication. The Health Belief Model method was used to assess ASGM workers' risk perception of mercury contamination. This study was conducted with the aim of analyzing the risk perception of mercury contamination among ASGM workers in Limun District. The research was conducted from May to July 2023 in four villages of Kecamatan Limun consisting of Pulau Pandan, Muara Limun, Temenggung and Moenti Villages with a phenomenological design. The research informants consisted of 15 people who were determined by purposive sampling technique. In-depth interview guidelines were used to determine miners' risk perceptions. Data were analyzed using the Miles and Hubberman method through three stages, namely reduction, presentation and conclusion drawing, triangulation of sources and methods was also carried out to test the validity of the data. The results showed that miners considered mercury contamination to have no impact on their health. Based on the seriousness of the impact factor, they consider that there has never been a serious illness due to the use of mercury in the mining process. Based on the barriers and obstacles factor, the benefits of mercury heavy metal use prevention behavior are also not the focus of miners. Based on the cues to action factor, they believe that the way of using and managing heavy metal mercury as taught to people around miners is correct, safe and will not have a serious impact on health. The perception of gold miners in Limun Sub-district towards mercury contamination shows a negative perception. There is a need for socialization, promotion and regular monitoring of the impact of mercury use on ASGM workers.